Kajian Integrasi Vertikal dan Dinamika Pasar Beras di Jawa Timur - Difah, Deby Ananda; Nurunisa, Venty Fitriany; Fitri, Annisa (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
This study aims to analyze the relationship of vertical integration in the rice market in East Java Province, involving the producer, wholesaler, and retailer levels. The main focus of this research is to analyze price transmission between different market levels and the interconnection among market players within the rice supply chain. The method used is secondary data analysis in the form of weekly time series from January 2020 to August 2024, applying the Vector Autoregression (VAR) model and the Augmented Dickey-Fuller (ADF) stationarity test. The analysis results show that rice prices between market levels influence each other in a bidirectional manner, with a significant long-term effect from retail prices. The wholesale market also plays a crucial role in price transmission between market levels. These findings reflect the complex rice market structure in East Java, which requires further attention in formulating pricing policies to achieve sustainable stability.